Apical Transportation of Mesiobuccal Canals of Maxillary Molars Following Root Canal Preparation with Two Rotary Systems and Hand Files: A Cone-Beam Computed Tomographic Assessment - Sarraf, Pegah (Front Dent, 2019)
OBJECTIVES: This study aimed to compare the transportation of the mesiobuccal canal of maxillary molars following root canal preparation with HyFlex CM (HCM) and Edge Taper Platinum (ETP) rotary systems and stainless steel (SS) hand files using cone-beam computed tomography (CBCT). MATERIALS AND METHODS: This in-vitro study was performed on 48 maxillary molars in three groups of 16. The teeth were mounted in acrylic blocks, and root canals were prepared using HCM in group 1 (up to #30/0.06), ETP in group 2 (up to F3/0.06), and SS hand files in group 3 (up to #30). CBCT scans were taken before and after root canal preparation. The amount of canal transportation was measured at 0, 3, 6, and 9mm from the apex. Data were analyzed using Kruskal-Wallis and Mann-Whitney tests. RESULTS: The difference in canal transportation at 0 and 6mm from the apex was significant between the HCM and ETP groups (P=0.031 and 0.023) but none of the systems showed any significant difference with hand files at 0-and 6-mm levels (P=0.10, 0.56, 0.22, and 0.50), respectively. At 3mm from the apex, no significant difference was noted among the groups (P=0.30). At the 9-mm level, the amount of canal transportation was not significantly different between HCM and ETP (P=0.83) but they showed significant differences with hand files (P<0.001). CONCLUSION: ETP and HCM caused less canal transportation at the curvature of the mesiobuccal canal of maxillary molars compared to hand files. ETP showed superior efficacy in root canal preparation compared to HCM.